Protection of Migrant Workers: A Study of International and Indonesian Law - Shavanita (Jurnal Pengembangan Ketenagakerjaan, 2024)
This study aims to analyze international law and Indonesian law which serve as guidelines for protecting migrant workers who experience problems that can harm these migrant workers. This research method uses Normative Juridical, namely by using secondary data as a research source which aims to examine legal issues based on existing norms in international law legislation and Indonesian law. The results of this study indicate that the role of international law and Indonesian law in protecting migrant workers can be shown through the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (ICRMW) and Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers. Where in these regulations it has been explained in detail what are the rights and obligations of migrant workers and their families, as well as what legal actions are taken if problems occur.